The hunt for planet X : new worlds and the fate of Pluto - Schilling, Govert (New York : Copernicus Books/Springer Science + Business Media, 2009)
"The Hunt for Planet X: New Worlds and the Fate of Pluto goes beyond a standard scientific read, encompassing who, and what, is involved in the pursuit of planetary endeavors. Touching on over three-hundred years of debates, debacles and discoveries, this book offers the reader insight into the minds and motives of planetary astronomers and their findings. The "hunt" continues to the outer-most regions of the solar system, and Govert Schilling states this search will not cease: "Astronomy is an adventurous science," he writes, and without adventure and those who seek it out the universe would otherwise remain mysterious. The real-life characters presented in The Hunt for Planet X look for glimpses of light in the dark, from Icy Kuiper Belt objects to full-fledged planets, in the process challenging how such worlds should be defined and ultimately describing the Universe."--BOOK JACKET.
A larger solar system -- Eleven planets -- The writing desk planet -- 'I've found your planet X' -- The kid planet -- A strange and wonderful week -- Fortunate circumstances -- Nix and hydra -- The unauthorized planet -- Uranus: problem solved? -- Mysterious forces -- The hunt for the death star -- The secret planet -- Vulcanoids and earth-grazers -- The Kuiper connection -- Comet puzzles -- Smiley -- Family portraits -- The migrating planet -- Icy treasure troves -- The big five -- The tenth planet -- The Spanish invasion -- Pas de deux -- Model from Nice -- Planet under siege -- Planetary elections -- The continuing story -- A thousand planets -- New horizons.
Includes bibliographical references (p. 295) and index.
Keywords: Planets -- Discovery and exploration -- Popular works; Outer planets -- Discovery and exploration -- Popular works; Astronomy -- History -- Popular works; Solar system -- Discovery and exploration -- Popular works